Performance analysis of elite women's wheelchair basketball players according to team-strength, playing-time and players' classification - Gomez, M. A.; Molik, B.; Morgulec-Adamowicz, N.; Szyman, R. J. (International Journal of Performance Analysis in Sport, 2015)
The aim of the study was to analyze the game-related statistics that best differentiate the performance of women's wheelchair basketball players according to team strength, playing time and players' classification. Thirty-three games from the World Wheelchair Basketball Championships (2010) were analyzed for this purpose. The official game-related statistics were studied (FIBA box-scores). Team strength (stronger and weaker teams), playing time (important and less important players), and player class (1, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, and 4.5 classes) were used as independent variables. The results from MANOVA showed greater differences between low and high point players for most of the game-related statistics. The stronger teams had better values in assists, turnovers, fouls received and successful free-throws. Playing time was significant for all the game-related statistics with the exception of blocks and successful 3-point field-goals. The main interactive effects were identified between team strength and class for defensive rebounds, assists, successful 2-points field-goals, and unsuccessful 3-point field-goals; between class and playing time for defensive rebounds, blocks, fouls on, successful free-throws and unsuccessful 2-point field-goals; between team strength and playing time only for steals; and between class, team strength and playing time for defensive rebounds and unsuccessful 3-point field-goal attempt.